2017
DOI: 10.5114/ada.2017.67843
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis pattern in Kuwait: nickel leads the pack. In-depth analysis of nickel allergy based on the results from a large prospective patch test series report

Abstract: A b s t r a c tIntroduction: Contact dermatitis is a relatively common dermatosis reported among several population groups from all around the globe. However, the data from Kuwait is unavailable. Patch tests are essential for the diagnosis of contact sensitization. Aim: To determine a relative frequency and pattern of sensitizers to different allergens in patients of suspected contact dermatitis in Kuwait and, also to study the role of the commonest sensitizer in detail. Material and methods: Patch tests were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…[14][15][16][17] Our frequency was similar to values from Italy (25.4%), Spain (25.4%), China (25.7% and 24.4%), and Kuwait (23.9%). [18][19][20][21][22] Second, frequency of nickel sensitivity significantly increased over the 12-year study period from 24.3% to 27.9% ( P < 0.001). Unfortunately, detailed analysis of trends in nickel sensitivity in Canada over time is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Our frequency was similar to values from Italy (25.4%), Spain (25.4%), China (25.7% and 24.4%), and Kuwait (23.9%). [18][19][20][21][22] Second, frequency of nickel sensitivity significantly increased over the 12-year study period from 24.3% to 27.9% ( P < 0.001). Unfortunately, detailed analysis of trends in nickel sensitivity in Canada over time is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…21,30,32,34 This has been suggested to be due to the decreasing incidence in piercings and reduced contact with imitation jewelry in older generations. 21 However, contrary to our results, other studies have found young age to be a prominent risk factor in nickel allergy with significantly higher prevalence of nickel sensitivity in pediatric patients compared with adults 19 years and older. 10,32 Unfortunately, with only 3.0% of our study population being pediatric patients, this population is underrepresented in our data set and likely lacks power to draw meaningful conclusions (Supplemental File 1, http://links.lww.com/DER/A84).…”
Section: Discussionmentioning
confidence: 99%
“…Nickel salts being soluble in water and sweat easily cause sensitization. The reason for the relatively high prevalence of nickel ACD could be the use of nickel in consumer items that come in direct and prolonged contact with the skin ( 15 ). However, exposure may also occur in certain occupational settings generally associated with soluble nickel salts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, according to a Danish study on current self-reported metallic exposures leading to dermatitis in nickel-allergic patients and the minimum contact time needed for dermatitis to occur, 21.4% of the patients reported dermatitis reactions within 10 min of contact, and dermatitis reactions within 30 min of contact were reported by 30.7% of patients [ 23 ]. In other regions of the world, such as Kuwait, nickel is a very important contact allergen, with 40% positive reactions in 2461 consecutively patch tested patients; the authors recommend adoption of nickel regulation limiting exposure [ 24 ].…”
Section: Resultsmentioning
confidence: 99%